How have foreign exchange market distortions and conflict affected agricultural production incentives in Myanmar? - Myanmar Agrifood Program for Strategy and Analysis (International Food Policy Research Institute, 2024)
Fluctuations in agricultural prices pose significant challenges for fragile and conflict-affected economies due to their critical role in ensuring food security. This study examines changes in agricultural prices at the export, wholesale, and farm level in the case of Myanmar, which experienced a surge in conflicts from 2021 onward, following a military coup. The major findings are as follows: • Regarding macroeconomic impacts, the military government implemented a dual exchange rate system, maintaining a fixed exchange rate significantly below the market rate and effectively imposing an across-the-board export tax on all export commodities of approximately 24 percent between August 2022 and August 2024. This policy particularly affects rice, Myanmar’s main staple and a key export crop. • The scarcity of foreign exchange due to this dual exchange rate system increased the costs of imported inputs. It is estimated that prices of inorganic fertilizers – farmers’ most important commercial input – saw an increase of 10 percent compared to the price in Thailand since the start of the dual exchange rate system. • Regarding domestic trade effects, regions with the highest insecurity exhibited similar agricultural output prices but higher input costs, resulting in reduced farm profitability compared to more secure regions. However, the magnitude of these effects is relatively small, with estimated increases in input prices due to insecurity ranging from one to six percent. Insecure areas also show more often a lack of input availability. • Farmers who reside in insecure areas reported between one and six percentage points higher lack of access to agricultural inputs – fertilizer, agrochemicals, mechanization, and seed - in their communities. The relatively small effects of insecurity on input and output markets suggest a degree of resilience in the private sector’s ability to maintain trade under conflict conditions. • The biggest effect on input markets is seen in the case of agricultural labor. Depending on the measure used, farmers in the most insecure areas had a 7 to 15 percentage points higher likelihood of reporting lack of access to agricultural laborers compared to the most secure areas. • The exchange rate policies are found to have been much more harmful for farmers’ incentives than the domestic trade effects, even for the most conflict-affected areas, indicating the importance of considering macroeconomic effects for agricultural incentives in Myanmar. • Despite the significant disincentives brought about by conflict, the agricultural sector has shown surprising resilience over the recent conflict period, seemingly linked to advantageous international price developments for farmers: international rice prices increased by 27 percent while urea prices decreased by 52 percent between August 2022 and May 2024. • While these international evolutions have partly mitigated the impact of the conflict on farmers’ profitability, the impacts of these price developments on consumers in Myanmar have, however, been severe. An analysis of rice retail prices in Myanmar over the last two and half years show that they have more than tripled and that the overall costs of the common diet more than doubled. A failure of nominal income to keep pace with this food price inflation led to an increase in poverty by 10 percent from the end of 2022 to the end of 2023.